Different factor VIII neutralizing effects on anti‐factor VIII inhibitor antibodies associated with epitope specificity and von Willebrand factor1. (24th July 2013) - Yada, Koji; Nogami, Keiji; Shima, Midori
Summary Inhibitor neutralization therapy based on factor (F)VIII replacement is used for haemostatic treatment in haemophilia A patients with inhibitors on low responder, but effects appear to depend on various properties of inhibitors. We investigated this nature by evaluating the global coagulation function in timed‐reactions after mixing FVIII (1 U/ml) with anti‐FVIII alloantibodies containing distinct epitopes (2·5 Bethesda units/ml). Thrombin generation assays showed that peak thrombin and mean velocity to peak thrombin were depressed by anti‐C2 type 1 inhibitors to significantly greater extents than by anti‐A2 type 1 and anti‐C2 type 2 (2‐ to 6‐fold and 10‐ to 20‐fold, respectively). In the presence of FVIII‐von Willebrand Factor (VWF) complex, the anti‐C2 type 1‐mediated decreased thrombin generation was reduced by 20–40%, reflecting the protective function of VWF. However, the activities of anti‐A2 type 1 were little affected, and that of anti‐C2 type 2 was rather enhanced by c. 2·5‐fold, relative to FVIII. Clot waveform analysis also showed similar patterns. Anti‐FVIII monoclonal antibodies with well‐defined characteristics demonstrated similar reactions to those with polyclonal inhibitors. In conclusion, the neutralizing effects of FVIII(‐VWF) depending on epitopes could have significant therapeutic implications, and it could be important to determine inhibitor properties in order to predict the effects of infused FVIII in neutralization therapy.